‘Hewmanity’ Versus Humanity: Tension and Social Vision in the Poetry of Joe Ushie and Ogaga Ifowodo - Eyang, Anthony Ebebe (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
Transcending the representation of social injustice and its myriad forms is the visioning of the future in the works of many Nigerian poets. This essentially gives a defining characteristic to Nigerian poetry by its inherent organicity with the socio-historical, political and material condition of the nation. In the climate of social injustice, corruption, underdevelopment and environmental neglect, the Nigerian writer cannot afford the luxury of disconnecting themselves and their works from these social concerns which have a deleterious impact on the quality of life. The paper interrogates the different modes of representation of social injustice, termed 'hewmanity' and the tension in the poetry of Joe Ushie and Igaga Ifowodo, both Niger Delta committed writers. The injustice and the tension lie in the relationship between those at the core and those at the periphery. The paper reasons that 'hewmanity' is an antithesis to the humanity we all share; thus ‘hewmanity’ is in this sense a mocking indictment of the failure to respond appropriately to the duty of service to our shared humanity. However, in this satirical representation of the downside of humanity, Ushie and Ifowodo express a strong social vision for the future – justice, harmony, and rationality, which come out of a collective resolve to bring about change. The call to the duty of humanity lies in the understanding that beyond agonizing is the imperative of organizing for the good of tomorrow. This is a strand common to Ushie and Ifowodo’s ideology. The paper concludes that the authorial ideology of the writer blends with the form and language to the effect that our imagined future lies in our readiness to act and address today’s injustice.